Social control: analytical tool or analytical quagmire? - Chunn, Dorothy E. (Contemporary crises, 1988)
In this paper we have undertaken what we regard as a preliminary critique of the concept of ‘social control’ and its utility for a critical criminology in Canada. In tracing its emergence and historical development as a key concept in American sociology, we have illustrated that its ascendancy represented a victory for liberal sociology. The recent attempts by critical criminologists and sociologists to rehabilitate the concept of ‘social control’ by insisting upon the essentially coercive nature of control have not resulted in an advance over traditional theorizing.By examining the ‘women, law and social control’ literature, in particular the use of the ‘formal/informal’ dichotomy, we have attempted to illustrate the limited utility of the concept for developing an historically and theoretically informed understanding of the complex and contradictory relationship of women to the state and law. The concept of ‘social control’ is ahistorical: when coupled with law, moreover, it lends itself to instrumentalism. It is our view that the concept of ‘social control’ ought to be abandoned by critical scholars in favour of one attentive to the dynamic complexity of history, struggle and change.